Preparation of ZnO Nanoparticles with Enhanced Antifriction Properties - Li, Wei; Zheng, Shaohua; Wang, Ping; Chen, Qiang; Song, Xiaoyun; Cao, Bingqiang (Asian Journal of Chemistry, 2012)
In this paper, the ZnO nanoparticles were prepared by a non-hydrolytic sol method. It was found that the mean particle size of ZnO nanoparticles was about 80 nm with a uniform distribution by the particle size analysis. The prepared ZnO nanoparticles can disperse in lubricating oil homogenously for several weeks. The reason is that the grafted polymers are introduced by nonhydrolytic sol method. The formation of covalent bands was identified by Fourier transform infrared spectrum. Under an optimized concentration of 1.5 wt %, the averaged friction coefficient was reduced by 8.42 %, when the ZnO nanoparticles sol was used as lubricating oil additives.